Comparative Evaluation of Fluoride-releasing Properties in Nano-formulated and Conventional Glass Ionomer Cements: An In-vitro Study - E Dhivyasri; Jessy Paulraj; Subhabrata Maiti (Journal of Clinical and Diagnostic Research)
Introduction: Numerous efforts have been made to enhance the properties of Glass Ionomer Cements (GICs) using nanotechnology. One of the most advantageous properties of GICs is their ability to release fluoride. Aim: To compare and evaluate the fluoride release in nano-formulated and conventional GICs. Materials and Methods: This in-vitro study conducted at the Department of Pedodontics, Saveetha Dental College and Hospitals, Saveetha Institute of Medical and Technical Science, Saveetha University, Chennai, Tamil Nadu, India, assessed the influence of Chitosan-Titanium-Zirconia-Hydroxyapatite (Ch-Ti-Zr-HA) nanoparticles on the fluoride-releasing ability of GICs. A Ch-Ti-Zr-HA nano formulation was synthesised using a single-step, green-mediated process and was incorporated into GICs at concentrations of 3%, 5% and 10% (Groups I, II and III), with conventional GIC serving as the control (Group IV). Specimens from each group (n=30) were immersed in 10 mL of deionised water in sealed polyethylene vials. Fluoride release was measured using a fluoride Ion-Selective Electrode (ISE) in combination with Total Ionic Strength Adjuster Buffer (TISAB). Measurements were taken at 24 hours, on the third, seventh, 14th and 28th days, using an ion analyser (Orion Star™ A214 pH/ISE Meter). Statistical analysis was performed using One-way Analysis of Variance (ANOVA), followed by Tukey’s post-hoc test to determine significant differences between the groups. Results: The nano-formulated GICs demonstrated higher fluoride release compared to conventional GICs at all time points. All samples initially showed high fluoride release, which gradually decreased over time. The total fluoride release increased from day 1 to day 28 across all concentrations of the nano-formulated GICs. Among these, the 10% concentration released a significantly greater amount of fluoride at every time point: 170.03±0.512 on day 1, 164.83±0.427 on day 3, 155.10±0.275 on day 7, 126.20±0.309 on day 14 and 76.16±0.107 on day 28, compared to the other groups (p-value <0.05). Conclusion: In all the experimental groups, the addition of the nano formulation to the GICs had an accelerating effect on their fluoride-releasing property.